2004
DOI: 10.1063/1.1774760
|View full text |Cite
|
Sign up to set email alerts
|

Study on Quench Protection of Coil Wound of Copper or Silver Stabilized YBCO Conductors

Abstract: We investigated necessary amount of copper or silver stabilizer added to YBCO conductor by numerical calculation to protect the conductor in a coil of dry windings from damages caused by quenches. The coil is assumed to be operated at 20K, 40K and 77K and hot-spot temperature of the conductor during energy dump sequence is calculated. The necessary amount of the stabilizer and overall conductor current density of the conductor including the stabilizer were calculated to suppress the hot spot temperature below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Details of calculation method are the same as in described in Ref. [7]. T HS is estimated from the calculated time evolutions of conductor temperature profile during sequence of quench detection and energy dump.…”
Section: Thermal Equilibrium Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of calculation method are the same as in described in Ref. [7]. T HS is estimated from the calculated time evolutions of conductor temperature profile during sequence of quench detection and energy dump.…”
Section: Thermal Equilibrium Equationmentioning
confidence: 99%
“…By attaching Cu stabilizer to wires, coils can be protected from damages suppressing T HS below safe level. Most works on the quench issues are devoted to protection and stabilization of quenches by the cause (a) [2][3][4][5][6][7][8]. In those works, however, relation between size of defects in HTS of coil wires and amount of the stabilizer is not well studied and criteria for stabilization relating to size of the defects are not clarified.…”
Section: Introductionmentioning
confidence: 97%
“…We did the calculation putting T c = 80 K and found that the results were not much affected by T c . Assuming that distributions of currents in the silver, copper layers and superconducting layer are uniform in the cross sections of the corresponding layers, an equivalent circuit model for current distributions in layers of the CC can be formed as shown in the reference [6]. In the calculation it is assumed "n" value of CC is high enough to assume that sharing currents in silver and copper layers I sh is 0 for I t < I c and (I t -I c ) for I t > I c .…”
Section: A Structure Of Model CCmentioning
confidence: 99%
“…W cool (W/m) is the heat conducted to and from the conductors of neighboring layers and put to zero in this analysis assuming the CC is thermally insulated. Details of the calculation are explained in the reference [6]. T HS is estimated from the calculated time evolutions of conductor temperature profile during sequence of quench detection and energy dump.…”
Section: A Structure Of Model CCmentioning
confidence: 99%
See 1 more Smart Citation